2020
DOI: 10.1177/1468087420921042
|View full text |Cite
|
Sign up to set email alerts
|

Understanding partial fuel stratification for low temperature gasoline combustion using large eddy simulations

Abstract: The development of gasoline compression ignition engines operating in a low temperature combustion mode depends heavily on robust control of the heat release profile. Partial fuel stratification is an effective method for controlling the heat release by creating a stratified mixture prior to autoignition, which can be beneficial for operation across a wide load range. In this study, three-dimensional large eddy simulations were used to model a double direct injection strategy for which 80% of the fuel was inje… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 56 publications
0
19
0
Order By: Relevance
“…The current paper extends the work of Priyadarshini et al 56 by evaluating two additional mechanisms and by extending the test matrix to include highly stratified conditions. Details on the validation of the CFD model can be found in Priyadarshini et al 56 The top row of Figure 4 shows the results for low stratification (SOI 2 = 2160 CAD aTDC). It can be observed that for all the combustion metrics, the model is in very good agreement with the experiments when SKM1 is used.…”
Section: Compositional Stratification Analysismentioning
confidence: 69%
See 1 more Smart Citation
“…The current paper extends the work of Priyadarshini et al 56 by evaluating two additional mechanisms and by extending the test matrix to include highly stratified conditions. Details on the validation of the CFD model can be found in Priyadarshini et al 56 The top row of Figure 4 shows the results for low stratification (SOI 2 = 2160 CAD aTDC). It can be observed that for all the combustion metrics, the model is in very good agreement with the experiments when SKM1 is used.…”
Section: Compositional Stratification Analysismentioning
confidence: 69%
“…Finally, it should be noted that the CFD model used in this investigation has been already validated by Priyadarshini et al 56 for low and moderate levels of stratification and using SKM1. The current paper extends the work of Priyadarshini et al 56 by evaluating two additional mechanisms and by extending the test matrix to include highly stratified conditions. Details on the validation of the CFD model can be found in Priyadarshini et al 56 The top row of Figure 4 shows the results for low stratification (SOI 2 = 2160 CAD aTDC).…”
Section: Compositional Stratification Analysismentioning
confidence: 97%
“…Then, a second injection supplies the remaining 20% of the fuel at a variable timing, SOI2, during the compression stroke. Experimental results 11,12 and computational fluid dynamics simulations 42,44 have shown that SOI2 = 200 CAD results in the most wellmixed charge (even more well mixed than earlier SOI2s). Variable levels of stratification were created by retarding SOI2 from 200 CAD to later crank angles.…”
Section: Results Under Partially Stratifiedmentioning
confidence: 99%
“…Custom fuels are compared to a surrogate fuel for a regular-grade, E10, AKI 88.4 (RON 92), research gasoline, known as RD5-87, the formulation of which is shown in Table . This surrogate was previously developed by the authors based on the actual fuel composition, and it was validated against experimental results under LTGC conditions. …”
Section: Numerical Methods and Fuel Specificationsmentioning
confidence: 99%
“…It raises the local mean equivalence ratio even further, resulting in slower and more fluctuated initial flame propagation. 14 Priyadarshini et al, 15 observed that when injecting too late, past 50°CA bTDC at 1200 rpm, the fuel is injected into a smaller cylinder volume. The benefits of the bulk flow motion are thus difficult to achieve.…”
Section: Introductionmentioning
confidence: 99%